The “Hungarian Barmen”. The Impact and Reception of the Declaration of Confession and the Barmen Declaration in Hungary - András CSŰRÖS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
Finding a way out by confession. In 1955, the Declaration of Confession, inspired by the Barmen Declaration, was drawn up in great secrecy and became one of the necessary documents of 20th-century Hungarian Reformed Christianity. In this study, we examine its reception and impact in Hungary. We will look at how the Barmen Confession appeared in Hungary and what influence it had on the 1955 Declaration of Confession.